#### Answer

x=0.5

#### Work Step by Step

Simplifying
4(x + 3) + -9(x + -2) = x + 27
Reorder the terms:
4(3 + x) + -9(x + -2) = x + 27
(3 * 4 + x * 4) + -9(x + -2) = x + 27
(12 + 4x) + -9(x + -2) = x + 27
Reorder the terms:
12 + 4x + -9(-2 + x) = x + 27
12 + 4x + (-2 * -9 + x * -9) = x + 27
12 + 4x + (18 + -9x) = x + 27
Reorder the terms:
12 + 18 + 4x + -9x = x + 27
Combine like terms: 12 + 18 = 30
30 + 4x + -9x = x + 27
Combine like terms: 4x + -9x = -5x
30 + -5x = x + 27
Reorder the terms:
30 + -5x = 27 + x
Solving
30 + -5x = 27 + x
Solving for variable 'x'.
Move all terms containing x to the left, all other terms to the right.
Add '-1x' to each side of the equation.
30 + -5x + -1x = 27 + x + -1x
Combine like terms: -5x + -1x = -6x
30 + -6x = 27 + x + -1x
Combine like terms: x + -1x = 0
30 + -6x = 27 + 0
30 + -6x = 27
Add '-30' to each side of the equation.
30 + -30 + -6x = 27 + -30
Combine like terms: 30 + -30 = 0
0 + -6x = 27 + -30
-6x = 27 + -30
Combine like terms: 27 + -30 = -3
-6x = -3
Divide each side by '-6'.
x = 0.5
Simplifying
x = 0.5